Les jeux de mots – déconstruction et reconstruction de sens - Georgiana, Burbea (Wydawnictwo Naukowe UAM, 2013)
The present study aims at analyzing puns from the front page of the newspaper Canard Enchaîné, more precisely the deconstruction of meanings and the reconstruction of new meanings by means of this linguistic process. As it is shown by the specialized literature, the nature of the pun itself actually reveals the lexical or semantic organization of all pre-constructed material. The puns used in our corpus will extend, as we shall see, from polysemy and ambiguity resulting from the multitude of meanings that a word can have, to the construction of portmanteau words: « Pour Standard et Poor’s : Cet accord Mercozy, c’est de la poudre de Berlinpimpin » (Canard enchaîné, 4754), the construction of new words : « Après l’annonce surprise du référendum le choeur des 26 européens : On s’est fait Papandréouter » (Canard enchaîné, 4749), to finally arrive at the use of defrosted structures, as in the example: « Sommet à Bruxelles pour sauver la Grèce et l’euro. L’Europe peine à reprendre du poil de la dette » (Canard enchaîné, 4734).
Pun and wordplay – deconstruction and reconstruction of meaning
Keywords: puns; portmanteau word; defrosted structures; polysemy; polylexicality